Re-organizing Universities for the Information Age - Annand, David (International Review of Research in Open and Distributed Learning, 2007)
University education is still generally conducted within pre-Industrial Age organizational structures. As a result of their inability to evolve the predominant cohort-based classroom structure to more cost-effectively meet the aspirations of burgeoning worldwide populations for higher education, universities may see substantial organizational changes imposed on them over the next decades by external forces. Emergent forms of university organizational structures are examined that may affect this needed transformation.